Application of Casein Phosphopeptide Isolate in Cheese as Dental Caries Prevention - Fathulhuda, Muhammad Muflih; Caroline, Cindy; Muthmainnah, Shafwah; Faridah, Didah Nur (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Dental caries is an infectious disease that results from bacterial interactions with teeth. One of the preventive effort against dental caries is consuming foods containing a bioactive compound called casein phosphopeptide (CPP). Cheese is one of the food products that contain CPP. This study aimed to measure the potential of CPP compounds obtained from cheese protein as a preventative for dental caries. This research was conducted from April to July 2019. The method used in this study was measuring the inhibition power on the growth of bacteria causing dental caries (Streptococcus mutans) and measure the process of teeth remineralization in vitro. The results showed that the yield of crude CPP isolates obtained from commercial parmesan cheese was 16.65 ± 2.97 %. CPP isolates inhibited the growth of S. mutans at concentrations of 10 %, 15 %, and 20 % with inhibitory zone values of 1.22 ± 0.04 cm, 1.30 ± 0.00 cm, and 1.36 ± 0.08 cm, respectively. The application of 0.1 g CPP isolates on tooth surface for 10 days was shown to increase tooth hardness by 28.36 %.